Windows web proxy caching simulation: a tool for simulating web proxy caching under windows operating systems - Yasin, Waheed; Ibrahim, Hamidah; Udzir, Nur Izura; Abdul Hamid, Nor Asilah Wati (Science Publications, 2014)
Web caching plays a key role in improving the performance of the web by reducing the latency of delivering web objects to the users. On the other hand, a simulation tool plays a key role in studying the behavior of any network such as studying the effects of web caching on the performance of the network. The aim of this work is to present a tool for simulating a web proxy caching for windows operating systems since there is no existing well-compatible simulation tool for windows operating systems that can simulate Hit Ratio (HR) and Byte Hit Ratio (BHR) for traditional caching policies. The proposed simulation tool is called Windows Web Proxy Caching Simulation (WWPCS). The results show the performance of traditional web caching policies for different caches sizes. Moreover, in order to show the efficiency of WWPCS, the results of running WWPCS are compared to the results of running a Unix-based tool.